Determinación de colesterol, C-HDL, C-LDL y Trigliceridos en pacientes diabéticos con antecedentes de enfermedad cardiovascular en el Hospital del Seguro Social de la ciudad de Machala - Garcia Burbano, Marlene N. (2008)
The cholesterol, C-HDL, C-LDL, and triglycerides the same as other biochemical parameters of clinical interest, are in the organism at level of the sanguine plasm in normal concentrations but in certain pathologies like in the diabetes and the illnesses vascular cardio, illness in which we have based our study realized that they can vary according to certain social and economic conditions.